Thinking about education as a constitutional right in Brazil in light of the awareness proposed by Paulo Freire: a counterpoint to the neoliberal vision of education (Olhar de Professor, 2025)
This article discusses the right to education, according to the 1988 Brazilian Constitution, as a guarantee for the realization of the democratic order. To this end, it draws on Paulo Freire’s views on education, namely: education as an emancipatory act, as a political act, and as conscientization. Next, the article discusses the challenge of overcoming a banking model of education in the prevailing context of neoliberalism, which reduces education to the status of a commodity. It seeks to draw a parallel between the works Conscientization, by Paulo Freire, and The School is not a Business, by Christian Laval, relating the challenge of achieving education that prepares individuals for the labor market while also fostering citizenship. In view of this, it is necessary to understand the rights enshrined in the Federal Constitution, including those related to education, and to rethink an education that is humanizing, emancipatory, and capable of overcoming the logic of oppression and the commodification of education.
Keywords: Education; Constitutional Right; Paulo Freire